2008
DOI: 10.1093/cvr/cvn243
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and non-apoptotic programmed cardiomyocyte death in ventricular remodelling

Abstract: A defining cellular event in the transition from compensated hypertrophy to dilated cardiomyopathy is cardiomyocyte drop-out due to apoptosis, programmed necrosis, and autophagy. The importance of apoptosis in heart failure has been recognized for over a decade, while other forms of programmed cell death have more recently been appreciated, and their pathophysiological roles continue to be defined in experimental and clinical heart failure. The major focus of this review is on apoptosis in heart failure, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
198
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(205 citation statements)
references
References 119 publications
2
198
0
5
Order By: Relevance
“…The rate of CM apoptosis in patients with diabetes is 85‐fold greater than that in nondiabetics (Ho, Liu, Liau, Huang & Lin‐Shiau, 2000). Diabetes‐induced CM apoptosis has been associated with excessive generation of reactive free radicals even though other inductive pathways exist as well (Dorn, 2009; Robertson et al., 2004). Increased ROS production and reduced antioxidant levels in diabetes have been widely documented in previous reports (Fiordaliso et al., 2004; Houstis et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of CM apoptosis in patients with diabetes is 85‐fold greater than that in nondiabetics (Ho, Liu, Liau, Huang & Lin‐Shiau, 2000). Diabetes‐induced CM apoptosis has been associated with excessive generation of reactive free radicals even though other inductive pathways exist as well (Dorn, 2009; Robertson et al., 2004). Increased ROS production and reduced antioxidant levels in diabetes have been widely documented in previous reports (Fiordaliso et al., 2004; Houstis et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a role for autophagy in programmed cell death type II (nonapoptotic death) in heart disease [15,16] and indicated that excessive autophagy could lead to cell death. Valentim et al [17] showed that inhibition of autophagy, by both genetic and pharmacological inhibition of Beclin 1, reduced cell death in cardiomyocytes subjected to simulated ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that calpain-1 is important in cardiomyocyte apoptosis and cardiac proinflammatory responses under pathological conditions (16 -19). Both apoptosis and inflammation contribute to post-MI remodeling (20,21). Thus, calpain may be implicated in myocardial remodeling.…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 99%